Psychological Differences of Economically Deprived Adolescents in Urban and Rural Areas - Maula, Atifatul; Nuryani, Reni; Lindasari, Sri Wulan (Indonesian Journal of Global Health Research, 2024)
Poverty is one of the causes of mental health problems for adolescents. Poverty can affect mental health indirectly through the environment and family upbringing. The area where adolescents live also contributes to the cause of mental problems. Poor adolescents in the wrong place to live can worsen mental conditions. Differences in residence also affect the differences in psychological problems experienced by adolescents. Psychological problems encourage suicide if not handled quickly. Two teenagers took their lives in village Brebes Regency due to economic deprivation. Objective: This study aim to determine the differences in psychological problems of depression, anxiety, and stress of adolescents with extreme poor families living in urban and rural areas. Method: This research is a comparative quantitative research. The type of research used is survey. This study used the DASS-21 questionnaire which was distributed offline. The population of this study were all poor adolescents in Prapag Kidul Village and Pasarbatang Village. Samples were taken using proportional random sampling. The total sample used in this study was 172 poor adolescents with details of 92 poor adolescents in rural areas and 80 poor adolescents in urban areas. Data were analyzed using descriptive and inferential Mann Whitney statistics. This study has received approval from the ethics commission with No. 128/KE.03/SK/12/2023. Results: The study revealed significant differences between depression, anxiety, and stress conditions of extreme poor adolescents in rural and urban areas with p values of depression 0.047, anxiety 0.01, and stress <0.01 respectively. Conclusions: Rural areas have more poor adolescents with psychological conditions of depression, anxiety, and stress than urban areas.